2014
DOI: 10.1007/s11274-014-1702-4
|View full text |Cite
|
Sign up to set email alerts
|

Breaking through the stress barrier: the role of BolA in Gram-negative survival

Abstract: The morphogene bolA plays a significant role in the adaptation of Escherichia coli to general stresses. In general, bacteria can thrive and persist under harsh conditions, counteracting external stresses by using varied mechanisms, including biofilm formation, changes in cell shape, size and protein content, together with alterations in the cell wall structure, thickness and permeability. In E. coli, an increased expression of bolA occurs mainly under stress challenges and when bacterial morphology changes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…In Escherichia coli, overexpression of bolA leads to a rounded morphology and induction of biofilm formation (38,39). bolA is normally expressed in the stationary phase but can be induced under stress conditions; therefore, the increased expression of bolA and its regulator, rpoS, under the stress condition of antibiotic therapy is consistent with previous studies (38,39). Also potentially affecting cell morphology could be the downregulation of genes involved in the biosynthesis of peptidoglycan, including murDGP, mraYZ, uppP, and dacC.…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli, overexpression of bolA leads to a rounded morphology and induction of biofilm formation (38,39). bolA is normally expressed in the stationary phase but can be induced under stress conditions; therefore, the increased expression of bolA and its regulator, rpoS, under the stress condition of antibiotic therapy is consistent with previous studies (38,39). Also potentially affecting cell morphology could be the downregulation of genes involved in the biosynthesis of peptidoglycan, including murDGP, mraYZ, uppP, and dacC.…”
Section: Discussionmentioning
confidence: 99%
“…Starved bacterial cells display tendency towards grouping: the failure to separate after division, described in (Wainwright et al, 1999), results in filamentous growth which conforms to the reports of UspE-dependent cell aggregation (Nachin, Nannmark & Nyström, 2005), and transcriptional factor BolA-mediated biofilm formation (Guinote et al, 2014;Dressaire et al, 2015) (both of the proteins were upregulated by starvation). Our 2D annotation analysis unequivocally showed that starved cells are enriched in 'Biological adhesion' GO term and thus Formation of cellular aggregates, such as biofilms, could serve as a defense mechanism against antibiotics as described in (Nguyen et al, 2011;Bernier et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Since BolA family proteins have been shown to participate in stress response pathways (2), we explored whether the absence of ibaG altered V. cholerae survival following exposure to a range of environmental stresses. Given results from studies of E. coli IbaG, we first assessed whether V. cholerae IbaG modulates growth or survival under acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
“… A . Coomassie Blue stained gel of proteins recovered after TAP purification from cell extracts of V. cholerae producing TAP-TAG only (1) or IbaG-TAP-TAG (2). Bands of interest were analyzed by mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation